RELASI CINTA DALAM TASAWUF - Suwito, Suwito (Jurnal THEOLOGIA, 2013)
Abstract: This article discusses the relationship of love in the Sufi perspective. Opositorum Coindencia theory is used to dissect this relationá¹¢ip , so that the devil Sufism is seen as a "sparring partner" in human spiritual quality improvement activities. This article shows that the Sufi tradition mainly in Waá¸¥dah al-WujÅ«d, using imaginal thinking mindset see and understand the duality (bipolar), even though this diversity is unity of opposites. In the context of Sufi, masculinityâ€”whichstated that the dominant sociologicalâ€”declared substantially have "weaknesses." Because masculinity will not appear if there is no femininity. While in the context of the birth of the universe and the form of anything that is in fact born out of the urge of love that goes on this feminine category. In other words, masculinity will not be born if it is not driven by the feminine aspect. This is the "mystery of immense power" aspect of femininity in Sufi discourse. Thus, there is nothing more superiority between these two aspects. Relation is equal based on and effect of love. Abstrak: Artikel ini membahas tentang relasi cinta dalam perspektif Sufi. Teori Coindencia Opositorum dipakai untuk membedah relasi ini, sehingga dalam Sufisme setan dipandang sebagai â€œsparing partnerâ€ manusia dalam melakukan kegiatan peningkatan kualitas ruhani. Artikel ini menunjukkan bahwa tradisi sufi terutama dalam tasawuf waá¸¥dat al-wujÅ«d, dengan menggunakan pola pikir imaginal thinking melihat dan memahami dualitas (bipolar), bahkan keragaman sekalipun ini adalah unity of opposites. Dalam konteks sufi, maskulinitasâ€”yang dinyatakan yang secara sosiologis dinyatakan dominan ituâ€” secara substansial memiliki â€œkelemahanâ€. Karena maskulinitas tidak akan muncul jika tidak ada femininitas. Sementara dalam konteks lahirnya wujud semesta dan apapun yang ada justru lahir karena dorongan cinta yang masuk pada kategori feminin ini. Dengan kata lain, maskulinitas tidak akan lahir jika tidak didorong oleh aspek feminin. Inilah â€œmisteri kekuatan dahsyatâ€ aspek femininitas dalam wacana sufi. Dengan demikian, tidak ada yang lebih superioritas antara dua aspek ini.Relasinya adalah setara berdasar dan akibat dari cinta. Keywords: Waá¸¥dah al-WujÅ«d, sufi, feminitas, maskuliniÂ¬tas, á¸¥ubb.